Childfree: A Field Research in X District - Khoiruddin, Khoiruddin; Alsayd, Abdulnasir (Anjasmoro: Islamic Interdisciplinary Journal, 2025)
The issue of child labor in Indonesia is covered in this article. To be child-free is for a husband and wife to have mutually agreed not to procreate while they are married. Just hearing the term "child-free" can make some people uncomfortable. Additionally, there is a tiny subset of society that has normalised and even engaged in this behavior, particularly among the well-to-do. Since bearing children and exercising reproductive rights in Islam are fundamental to the purpose of marriage, it is intriguing to examine this research from a scientific perspective. Childfree is the topic of this essay, which seeks to investigate the opinions and reactions of various Islamic groups in X District. Field research is utilized in this study to gather qualitative data. This study aims to examine the perspectives and reactions of Islamic organizations in X District about child-free activities. Several Islamic groups in X District were surveyed to get the necessary data. Then, descriptive analysis is used to examine the data. Based on the research, we know that (1) childfree is a phenomenon of contemporary issues that elicits mixed reactions (some people favor it, some don't), and (2) childfree is a form of radical feminism. Childfree, according to Islamic groups in X District Regency like Hidayatullah, Indonesian Islamic Da'wah Institute, Muhamadiyah, and Nahdlatul Ulama, is immoral since it contradicts Islamic teachings about marriage and the nature of human sexuality.